PENERAPAN SUPERVISI KUNJUNGAN KELAS UNTUK MENINGKATKAN KEMAMPUAN GURU MATEMATIKA DALAM MELAKSANAKAN PEMBELAJARAN DI SMA BINAAN KABUPATEN LAMONGAN - Salamun Salamun (MEDIA DIDAKTIKA, 2016)
The purpose of this research is to improve the ability of Mathematics teachers in preparing learning plans, in Developing Target Schools at KabupatenLamongan on Odd Semester, 2015/2016 Academic Year. The research design of school action consisted of 3 cycles. Subjects/research respondents are twenty high schoolmathematics teachers scattered in Developing Target Schools. Methods of data analysis using descriptive statistical analysis techniques scoring which is then converted intovalue. Indicators of success of this research to cycle 1, cycle 2 and cycle 3 is a minimum of 85% of respondents reached a value of at least 75. The results showed, in the firstcycle of many teachers who have reached a value of 75 there are as many as 17 people or reaches 85%. In the second cycle of many teachers who have reached a value of 75there are as many as 18 people or 90%. While in the third cycle of many teachers who have reached a value of 75 there are as many as 17 people or reaches 85%. Whencompared with the success indicators in cycle 1, cycle 2 and cycle 3, then three cycles may be said to be successful. It can be concluded that, implementation of supervisionclassroom visits can improve math teachers in implementing the learning plans.